The Intergenerational Transmission of Poverty in Industrialized Countries - Stephen P. Jenkins; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper reviews research about the intergenerational transmission of poverty in industrialized countries. In order to make our survey manageable, we restrict attention to studies that consider the relationship between parental poverty (or ?income?) during childhood and laterlife outcomes; we do not explicitly consider the impact of other family background variables such as parental education. The general message is that growing up poor has a deleterious impact on later-life chances, and that this impact is not wholly explained by other factors that are themselves correlated with childhood poverty. At the same time, the studies also show that one should be cautious about drawing more specific conclusions. For example, the degree of intergenerational persistence appears to vary depending on the definition of the outcome variable, and different estimation methods provide a range of estimates. In addition, most of research about intergenerational links has been undertaken using US data, and it is not clear that any specific conclusions should carry over to another country with very different social norms and institutions including e.g. differences in labour market regulation, and in systems of education and social security benefits. However we conclude that, broadly speaking, the analytical framework that has been used for high-income countries can also be applied to lowincome countries.
Keywords: 330; Poverty; intergenerational transmission; mobility; family background; income; industrialized countries; Armut; Generationenbeziehungen; Familiensoziologie; Soziale Mobilität; Industriestaaten; USA